THE EFFECT OF SCAFFOLDING AND PORTFOLIO ASSESSMENT ON JORDANIAN EFL LEARNERS’ WRITING - Bataineh, Ruba Fahmi; Obeiah, Salameh Fleih (Universitas Pendidikan Indonesia, 2016)
This study examines the potential effect of scaffolding-based instruction and portfolio-based assessment on Jordanian EFL tenth grade students’ overall writing performance and their performance on the sub-skills of focus, development, organization, conventions and word choice. The study uses a quasi-experimental experimental/control group, pre-/posttest design. In the experimental group, 15 female tenth grade students from the North-Eastern Badia Directorate of Education (Jordan) were taught to generate ideas, structure, draft, and edit their written pieces using agency scaffolding, the scaffolding principles of contextual support, continuity, intersubjectivity, flow, contingency and handover, and a slightly adapted version of Hamp-Lyons and Condon’s (2000) Portfolio Model of collection, selection and reflection. A control group of 28 students were instructed conventionally per the guidelines of the teacher’s book. Using descriptive statistics and ANCOVA to analyze the students’ scores on the pre- and the posttests, the results showed that the group taught through scaffolding-based instruction and portfolio-based assessment outperformed the control group (at a≤ 0.05) in their overall writing performance and in their performance on the five writing sub-skills.